Editorial - Green, Prof S (Social Work/Maatskaplike Werk, 2018)
The success of social welfare intervention services depends on the implementation of strategies geared towards the development of human potential and the capacity of communities. These services are rendered at different levels of intervention for diverse target groups and have specific outcomes in mind. Against this background, the articles presented in this issue of Social Work/Maatskaplike Werk include the response of social work at different levels of intervention to the needs of target groups such as women, families, parents, children, offenders and caregivers.